(untitled) (Taqdir, 2024)
Madrasah Aliyah Darussalam Sengon Jombang is a Madrasah that emphasizes on its students being able to carry out conversations using Arabic so there is a special program that teaches this, but up to now there are still difficulties in teaching students to be able to construct Arabic conversations through sentences. Indonesian sentences. For this reason, the activity of composing Arabic conversations through Indonesian-Arabic translation at MA Darussalam Sengon Jombang was held so that after participating in this activity students can have the skills and competence to compose Arabic conversations through translation of Indonesian texts, and they can practice it directly in in front of other students which can later be put into practice in daily conversations in the Madrasah environment. The research approach used by researchers is a qualitative descriptive approach. With this, researchers want to see incidents and events that are of interest to the images at the research location. The descriptive approach itself is research that simply describes a variable relating to the problem being studied without questioning the relationship between variables. Meanwhile, the qualitative method is a research method used to examine the condition of natural objects, where the researcher is the key instrument. . The results of this research are that students can translate Indonesian conversation texts into Arabic, students can have Arabic conversations by translating Indonesian sentences first, and students can solve the difficulties they experience when having conversations by translating Indonesian text into Arabic.